2017
DOI: 10.1002/2016ja023307
|View full text |Cite
|
Sign up to set email alerts
|

Observations of ion‐neutral coupling associated with strong electrodynamic disturbances during the 2015 St. Patrick's Day storm

Abstract: We use incoherent scatter radar observations at Millstone Hill (MHO) and Arecibo (AO) and topside ionosphere in situ Defense Meteorological Satellite Program (DMSP) observations during the great geomagnetic storm on 17–18 March 2015 to conduct a focused study on ion‐neutral coupling and storm time ionosphere and thermosphere dynamics. Some of these observations were made around the time of large ionospheric drifts within a subauroral polarization stream (SAPS). During the storm main phase, we identify multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
76
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 74 publications
(117 reference statements)
16
76
0
Order By: Relevance
“…Rapid postflare responses in neutral density were also observed previously (Liu et al, ; Sutton et al, ). The intensity of the observed vertical drift enhancement is comparable to geospace storm induced large ionospheric up‐welling at subauroral latitudes (Zhang et al, ). F region heating effects caused by geomagnetic activity have also been noted previously (Deng et al, ; Heelis & Coley, ).…”
Section: Further Discussionsupporting
confidence: 56%
“…Rapid postflare responses in neutral density were also observed previously (Liu et al, ; Sutton et al, ). The intensity of the observed vertical drift enhancement is comparable to geospace storm induced large ionospheric up‐welling at subauroral latitudes (Zhang et al, ). F region heating effects caused by geomagnetic activity have also been noted previously (Deng et al, ; Heelis & Coley, ).…”
Section: Further Discussionsupporting
confidence: 56%
“…This storm time disturbance neutral winds maximized to 100–250 m/s in westward and 200–300 m/s in equatorward [ Tulasi Ram et al ., , Figure 5]. Zhang et al [] have shown strong equatorward neutral wind surge (> 200 m/s) from the Millstone Hill radar in the dayside (American sector) consistently with nightside observations of Tulasi Ram et al []. Huang et al [] have also reported that there was a disturbance dynamo process initiated 3–4.7 h after the onset of the storm main phase and lasted for 31 h. Hence, it is expected that strong equatorward and westward neutral wind disturbance is also operating in the dayside Brazilian sector.…”
Section: Discussionsupporting
confidence: 54%
“…Similar but persistent T i and V los increases due to frictional heating have also been observed during the main phase of the same storm but in the subauroral polarization stream (SAPS) region by the Millstone Hill radar [Zhang et al, 2017]. Significant and persistent frictional heating can also increase the neutral temperature and lead to neutral upwelling, as found in the SAPS region by Zhang et al [2017]. However, because the neutrals need much longer time (tens of minutes to days) to respond to frictional heating [Schunk and Nagy, 2009], it is unlikely to have such neutral upwelling formed within the first 5-10 min right after the onset of the strong horizontal flows due to the SC.…”
Section: Magnetometer and Pfisr Observationssupporting
confidence: 64%
“…The T i increase occurred at the same time as the SC-related convection flow speed increase, and therefore, this increase is likely due to enhanced frictional heating. Similar but persistent T i and V los increases due to frictional heating have also been observed during the main phase of the same storm but in the subauroral polarization stream (SAPS) region by the Millstone Hill radar [Zhang et al, 2017]. Significant and persistent frictional heating can also increase the neutral temperature and lead to neutral upwelling, as found in the SAPS region by Zhang et al [2017].…”
Section: Magnetometer and Pfisr Observationssupporting
confidence: 62%
See 1 more Smart Citation